2017
DOI: 10.1097/md.0000000000007585
|View full text |Cite
|
Sign up to set email alerts
|

The safety and effectiveness of robot-assisted versus laparoscopic TME in patients with rectal cancer

Abstract: Background:The aim of this study was to assess the safety and effectiveness of robotic-assisted versus laparoscopic total mesorectal excision (TME) in patients with rectal cancer.Methods:We systematically searched PubMed, EMBASE, Cochrane library, Web of science, and Chinese Biomedical Literature Database up to July 2016 to identify case-controlled studies that compared robotic TME (RTME) with laparoscopic TME (LTME) for rectal cancer. GRADE was used to interpret the primary outcomes of this meta-analysis.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
65
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 46 publications
11
65
0
1
Order By: Relevance
“…Our study showed that the rate of positive CRM was 4.85% in the RRCS group and 5.39% in the LRCS group; therefore, RRCS or LRCS did not significantly improve the CRM‐related outcomes. This result was consistent with results from two meta‐analyses published in 2017 . Previous meta‐analyses included studies with mixed designs, and one meta‐analysis based on RCTs only pooled data from two studies that had reported this parameter.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study showed that the rate of positive CRM was 4.85% in the RRCS group and 5.39% in the LRCS group; therefore, RRCS or LRCS did not significantly improve the CRM‐related outcomes. This result was consistent with results from two meta‐analyses published in 2017 . Previous meta‐analyses included studies with mixed designs, and one meta‐analysis based on RCTs only pooled data from two studies that had reported this parameter.…”
Section: Discussionsupporting
confidence: 89%
“…This result was consistent with results from two meta-analyses published in 2017. 15,35 Previous meta-analyses included studies with mixed designs, 14,33,35 and one meta-analysis 15 based on RCTs only pooled data from two studies that had reported this parameter. Because our meta-analysis included newly published RCTs, 13,25,27 which resulted in a larger sample size and statistical power, the results of our meta-analysis can therefore be considered more credible.…”
mentioning
confidence: 99%
“…Recent meta‐analyses have shown inconsistent conclusions in terms of postoperative complications. Several studies have shown no significant difference in the frequency of postoperative complications or length of hospital stay between RALS and CLS . In contrast, two studies showed fewer postoperative complications and a shorter length of hospital stay in RALS than CLS .…”
Section: Short‐term Outcomesmentioning
confidence: 97%
“…Several studies have demonstrated that RALS is a safe and feasible approach in various colorectal procedures; however, robust clinical evidence supporting the benefit of robotic‐assisted surgery for rectal cancer remains limited. The results from recent RCTs and meta‐analyses of RALS vs CLS or OS for rectal cancer are summarized in Table . Several recent meta‐analyses have shown a significant difference in the outcomes between RALS and CLS for rectal cancer, including the rates of conversion to OS and positive CRM.…”
Section: Short‐term Outcomesmentioning
confidence: 99%
“…With the development of digital medicine and minimally invasive surgery, digital minimally invasive technology came into being, refers to the three-dimensional reconstruction, visual simulation surgery and other digital medical technology applied to surgical clinical work, to achieve surgical minimally invasive [2] . Since the 20th century, 90 years, a combination of computer image processing and analysis, realistic computer graphics, virtual reality and other technical image of the three-dimensional visualization technology has been a hot research and application at home and abroad, in the past 10 years The rapid development [3] .…”
mentioning
confidence: 99%